Theory of Disk Accretion onto Magnetic Stars - Lai Dong (EPJ Web of Conferences, 2014)
Disk accretion onto magnetic stars occurs in a variety of systems, including accreting neutron stars (with both high and low magnetic fields), white dwarfs, and protostars. We review some of the key physical processes in magnetosphere-disk interaction, highlighting the theoretical uncertainties. We also discuss some applications to the observations of accreting neutron star and protostellar systems, as well as possible connections to protoplanetary disks and exoplanets.